Food security and nutrition in Cambodia: Pattern and pathways: A policy discussion paper - Ecker, Olivier; Diao, Xinshen (Cambodia Development Resource Institute (CDRI), 2011)
This paper provides an overview of the food security and nutrition situation in Cambodia. From a regional perspective and through comparison with its neighboring countries and other countries in Asia, the paper analyzes the patterns of the hunger and malnutrition problem in Cambodia and possible pathways the country could follow in the future. Between China and Vietnam on the one side and India on the other side, the relationship between economic growth and the process of nutrition improvement diff ers greatly. We expect that these comparisons will help Cambodia identify a development pathway to let economic growth better trickle down to the impoverished population and significantly reduce poverty, hunger and malnutrition in the growth process.